SOLAR ENERGY AS A DRIVER OF SUSTAINABLE DEVELOPMENT IN AGRICULTURE: POTENTIAL AND LEGAL FRAMEWORK FOR IMPLEMENTATION IN THE REPUBLIC OF SERBIA - Ljubojev, Nadežda; Dukić Mijatović, Marijana; Pekez, Jasmina (Economics of Agriculture, 2024)
The authors analyze two very important topics, which are intertwined, and relate to the legal regulation and application of solar energy in agriculture in our country. Solar energy reduces the costs of agricultural production in the long term and increases sustainability and competitiveness. Therefore, when it comes to the application of solar energy in agriculture, an important factor that directly affects market positioning is the greater competitiveness of food produced using clean energy. In addition, legal frameworks significant for the use of solar energy in agriculture at the European level and within the borders of the Republic of Serbia were considered as the subject of the paper. The Republic of Serbia has real potential for the production and application of solar energy, but these potentials are not sufficiently used, and the experiences of EU countries can be significant when adopting measures from the sphere of energy policy, especially if one takes into account the context of European integration in accordance with environmental protection.